Causes of Early Marriage on Socio-Ecological Levels - Ucca Fajrin Wicitra Putri; Budi Prasetyo; Lutfi Agus Salim (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
A quantityof child brides in the world is currently estimated at 650 million and UNICEF (2018) recommends that to end the practice of child marriage by 2030 according to the SDG's target, progress in reducing child marriage rates must be accelerated significantly, which is 12 times faster or more than 150 million additional girls will be married before their 18th birthday in 2030. Approaches from various socio-ecological levels can help understand a phenomenon in society and the impact of potential prevention strategies.  Methods: This study uses a review of international articles.  The articles used are sixteen articles published in the last ten years.  Result: Individual levels that impacts early marriage are education, internal factors, and Working female job status.  At the Relationship level that affects the level of education and religiosity of spouses and families, Parental roles and autonomy in decision-making, wealth, Relationships between 2 families, girls' high-risk sexual relationships.  At the Community level, the influencing factors are social stigma, agents of solicitations for early marriage proposals, and Disappointment with continuing education.  At the Societal level, the influences are geographic location, social culture, and legislation. Conclusion: The causes of early marriage are interrelated and influence each other at each level, both at the individual, relationship, community and societal levels.  For this reason, it is hoped that women and children observers as well as the government can carry out comprehensive interventions through a socio-ecological approach in an effort to reduce the number of early marriages so that the Millennium Development Goals are achieved.